Insight of precursor concentration, particle size and band gap of zirconia nanoparticles synthesized by co-precipitation method - Bhujel, Arun; Sapkota, Bibek; Aryal, Ram Lochan; Poudel, Bhoj Raj; Bhattarai, Sitaram; Gautam, Surendra K. (BIBECHANA, 2021)
Zirconia (ZrO2), an inorganic material, is a very fascinating material due to its high mechanical strength and fracture toughness. The synthesis is carried out by using the co-precipitation method using optimum content of zirconium oxychloride octahydrate (ZrOCl2.8H2O) with NaOH solution at a calcination temperature of 700°C. The synthesized samples were characterized to ensure structural, functional, morphological, and chemical composition by several techniques. The monoclinic structure has been confirmed from XRD, SAED, and Raman spectra. The Zr-O stretching vibration and Zr-O2-Zr bending vibrations were confirmed through FTIR analysis. The well-dispersed particles with spherical morphology were established through SEM and TEM analyses. EDX spectra confirmed the formation of pure zirconium oxide. The bandgap was calculated with the help of UV-Vis spectra and particle size was determined from XRD data using Debye Scherrer’s equation. The variation of bandgap and particle size compared with different concentrations of precursor solution was studied. BIBECHANA 18 (1) (2021) 1-9